Extra-adrenal Paraganglioma: An Uncommon Cause of Secondary Hypertension in a Young Subject - Kota, SK; Kota, SK; Jammula, S; Panda, S (Journal of Nepal Paediatric Society, 2011)
An 8 year boy was admitted with features of tuberculous meningitis. He was detected to have hypertension. Further investigations revealed an extra-adrenal paraganglioma. Tuberculous meningitis and paraganglioma could be chance associations. Paraganglioma is a rare and potentially lethal cause of secondary hypertension, very uncommon at this age. If left untreated it leads to complications arising from unrelenting hypertension. We report a case report on this very rare disease of paraganglioma presenting in an unexpected way. Key words: Paraganglioma; Tuberculous meningitis; Secondary hypertension DOI: http://dx.doi.org/10.3126/jnps.v31i3.4965 J Nep Paedtr Soc 2011;31(3): 238-240